What Do Labour Economics and Industrial Relations Have to Say to Each Other? - Gunderson, Morley (Relations industrielles / Industrial Relations, 2023)
Mutual gains can be made through greater cross-pollination between labour economics and industrial relations. The paper is organized around common criticisms of labour economics, with examples from industrial relations. Such criticisms, and their underlying principles, often explain important concepts in industrial relations, which can provide insights that may enhance labour economics. The intent here is to apply a forward-looking lens to advance theoretical and empirical reflection on current and future aspects of work and employment.SummaryLabour economics has evolved from an earlier emphasis on institutions and descriptive analysis, which it shared with industrial relations, to its current emphasis on rigorous theory and empirical techniques, which it now shares with economics. Common criticisms of labour economics are highlighted in this paper, with examples from industrial relations. The criticisms include: making unrealistic assumptions; assuming that everyone is rational and has perfect information; relying on exit as the device to discipline markets; ignoring voice and loyalty; having a quantitative orientation that assumes everything can be quantified and analyzed from cause to effect; being imperialistic and thinking that economics can be applied to all elements of human behaviour; ignoring power imbalances, historical determinism and institutions; being obsessed with outlining unintended consequences of well-intended policy initiatives; ignoring the internal labour markets within firms; being obsessed with efficiency; ignoring important issues of distribution and equity; dealing only with the effects on private parties; ignoring broader effects on society at large; and operating in a silo and ignoring other disciplines.While defending labour economics from those criticisms, industrial relations applies a forward-looking lens to advance theoretical and empirical reflection on current and future aspects of work and employment by highlighting the mutual gains that can be had from labour economics incorporating principles that are well established in industrial relations, such as inequality of bargaining power, importance of voice and loyalty, inductive reasoning through qualitative analysis and narratives and use of mixed methods that involve both quantitative and qualitative analysis. Industrial relations can benefit from principles of labour economics both empirically and theoretically, since empirical work is essential to test and advance theory. Specific examples from the literature are given to illustrate how each field can contribute to the other.